Análisis de la pesca artesanal realizada en Puerto Bolívar - Vivar Briceño, Rómulo Guillermo (2010)
Taking into account the importance of artisan fishery in Ecuador and the necessity for provide strategies for the development of the communities related to the greatest advantage of the fi-shery resources at Puerto Bolivar parish, belonging to Machala canton, El Oro province, it was carried out an analysis of the artisan fishery from March to December 2007, with the fol-lowing objectives: to obtain a monthly average for the artisan fishery landings at Puerto Boli-var; to determine which are the fishing skills used at the site and to calculate the cost of opera-tion of the small artisan fishery ship. For the development of this project, there were deter-mined the following variables: monthly landings, fishing skills, costs of operation, fishing ef-fort and types of ships, whit the aid of interview forms, divided in three parts: register of the shipper fishing departure; capture, effort and fishing skills, and records and costs of operation (ship-departure).The information obtained from march until December 2007 was entered in a data base, in which, by mean of a statistical calculation, determined the capture average car-ried out by each ship. From this process, the following conclusions were obtained: May, June and December are the months of higher capture, and the fish species gathered were: white sea-bass, plumero catfish, menudo, sting ray and coto catfish; as related to fishing skills, the so named bottom mesh method obtained the higher captures and the species gathered with this method of fishing were menudo and white sea-bass; the months with higher costs of operation were May, June and December, which recorded a higher average of capture due to a higher number of departures hence higher operative costs, the fishing effort more effective is the one which does not require many casts or more time for waiting, and as an example we have that a cast at one effective hour obtained a higher fishing results; the ships more used were the sim-plest ones as canoes and fiberglass boats with low propulsion (outboard engines), and the higher amount of captures was leaded by the above mentioned